Inklusivitas dalam Pembelajaran Bahasa Isyarat Indonesia di SLB Negeri Selong - Rita Kartika Murni; Padlurrahman Padlurrahman; Baiq Rismarini Nursaly (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
This study aims to identify the importance of learning Indonesian Sign Language for deaf students at SLB Negeri Selong, East Lombok, as well as to analyze the factors influencing the implementation of inclusive education based on Indonesian Sign Language. This research uses a qualitative approach with a case study method, involving students, parents, and teachers as the research subjects. Data were collected through interviews, observations, and questionnaires. The results indicate that learning Indonesian Sign Language is crucial in enhancing the communication skills of deaf students, both at school and at home. Most students feel that Indonesian Sign Language facilitates their communication, boosts their self-confidence, and supports active participation in social and academic life. However, there are still challenges in teaching Indonesian Sign Language, particularly related to limited support at home due to parents' lack of understanding of the language. Additionally, while learning at school has been relatively effective, students feel they still need more time and resources to fully master Indonesian Sign Language. This study highlights the importance of parental involvement and support from the community, as well as the need for further training for teachers and parents to support the development of Indonesian Sign Language for deaf students.